2019
DOI: 10.18632/aging.102271
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TUG1 enhances chemosensitivity in non-small cell lung cancer by impairing microRNA-221-dependent PTEN inhibition

Abstract: Long non-coding RNA taurine up-regulated gene 1 (TUG1) emerges as new players in gene regulation in several cancers; however, its mechanism of action in non-small cell lung cancer (NSCLC) has not been well-studied. Herein, we determined expression pattern of TUG1 in NSCLC and further identified its effect on the chemosensitivity of NSCLC. Low expression of TUG1 was found in NSCLC tissues obtained from non-responders to platinum-based chemotherapy and reflected poor overall survival. TUG1 overexpression was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 34 publications
(39 reference statements)
3
41
0
1
Order By: Relevance
“…10 Studies based on transcriptomics and genomics show that approximately 75% of human DNA transcribed to RNA is not translated into protein. 11,12 Many such RNA sequences exceed a length of 200 nucleotides and are termed long non-coding RNAs (lncRNAs). Several investigative reports applying various experimental techniques have demonstrated that these lncRNAs influence many essential physiological functions, including the differentiation of cell lineages 13,14 and immunological reactions.…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies based on transcriptomics and genomics show that approximately 75% of human DNA transcribed to RNA is not translated into protein. 11,12 Many such RNA sequences exceed a length of 200 nucleotides and are termed long non-coding RNAs (lncRNAs). Several investigative reports applying various experimental techniques have demonstrated that these lncRNAs influence many essential physiological functions, including the differentiation of cell lineages 13,14 and immunological reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, TUG1 was characterized as a new oncogene and found to be upregulated in multiple human cancers (50)(51)(52)(53)(54)(55)(56). TUG1 was upregulated in OC tissues and cells and was positively correlated with advanced disease and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, lncRNA TUG1 emerges as a new player in gene regulation in lung-related diseases (29)(30)(31). Many studies have indicated that TUG1 is downregulated in lung-related diseases, including acute lung injury (ALI) (29) and non-small cell lung cancer (NSCLC) (32).…”
Section: Discussionmentioning
confidence: 99%